Past, Present and Future Perspective of Artificial Intelligence in Healthcare and Nanotechnology: A Communication - Mansi Jain; Sakshi Vats; Chhavi Pahwa; Aksh Chahal; Kamran Ali (Journal of Clinical and Diagnostic Research)
Artificial Intelligence (AI) is an emerging technology that has the potential to impact all professions, including medicine and medical education. Over the last decade, there has been a multiple-fold increase in the use of AI tools in medical allied sciences and rehabilitation, as well as in nanotechnology research. This paper highlighted some of the AI-based outcomes in bioengineering, neuroscience, and related disciplines. In addition, current trends and future perspectives of AI-based applications will also be discussed. Consequently, fundamental concepts in AI, its contributions, and the promise of nanotechnology coupled with AI will be summarised.